Success Determinants of Private Labels in Nigeria: A Study of Selected Motorcycle Private Labels - Olise, Moses C.; Nkamnebe, Anayo D. (European Scientific Journal, ESJ, 2018)
This study examined the success determinants of private labels in Nigeria: A study of selected motorcycle private labels. The study, modelled variables like market context (rate of expansion), private label phenomenon, retailer- manufacturer relationship (Manufacturers willingness to supply), brand development, sales performance, price and government regulation to ascertain how they have influenced the success of private labels in the motorcycle industry using the Incremental and Radical Innovation and Cumulative Change and Punctuated Equilibrium theories. The study adopted a descriptive survey research design that aimed to determine the relationship between the independent variables and dependent variable in a population. The population of this study was made up of 2977 registered members of motorcycle private label owners in Anambra and Enugu states. A sample of 353 was determined for the study using Taro Yamane formula. A structured questionnaire was administered to 353 respondents but only 348 responded to the questionnaire. The data collected using the questionnaire were analyzed using descriptive statistics like frequency, mean and standard deviation; and also inferential statistics such as factor analysis and regression analysis. All analysis was conducted using SPSS version 23. Findings show that: private label phenomenon, retailer manufacturer relationship, Sales Performance, price, and government regulation are significant success determinants of private labels in the motorcycle industry. While, private label market context and brand development are not significant but they have positive relationship with successful private labels in the motorcycle industry. Based on the findings of this study, the following recommendations were made: With respect to Private Label Market Context, the study recommends that there is a need for the development of advanced private label program in terms of quality and market share by the ministry regulating trade and commerce in Nigeria. The entrepreneurs need to sustain the Private Label Phenomenon since it has a direct and positive relationship with successful private labels and it has also been confirmed that private label phenomenon has significant influence on the success of motorcycle Private Labels among others.